Influence of material anisotropy on fatigue crack growth in C–Mn steels of existing structures. Issue 11 (29th June 2020) - Slot, Henk; Nicoreac, Monica; Maljaars, Johan
Abstract: Rolled steel plates and sections are often applied in structures in such a way that the principal load direction corresponds with the rolling direction. Examples are beams, arches, or pylons of bridges, supporting beams of ship decks, and the main elements of crane structures. However, some types of structure are subjected to a multiaxial stress state or are loaded with the main load direction perpendicular to rolling. The orientation may influence the mechanical properties. This paper studies the influence of anisotropy observed in the microstructure of rolled C–Mn steels on the tensile properties, Charpy impact values and particularly the fatigue crack growth rates. The influence of anisotropy is determined through tests performed at different orientations with respect to the rolling direction, namely, L‐T, T‐L and T‐S orientations. Samples were taken from structures that were constructed between 25 and 50 years ago from steel grades Fe510C or St52.3 (modern equivalences S355J2 or S355N). The orientation appears to have a statistically relevant influence on Charpy impact value and fatigue crack growth rate. The anisotropy ratio, defined as the ratio between the mechanical property in a certain orientation with that of the L‐T orientation, ranged between 0.30 and 0.53 for Charpy impact values. The anisotropy ratios appear correlated with the absolute Charpy value, with a correlation coefficient of ρ = −0.8. The anisotropy ratios of the crack growth in T‐L and T‐S orientations were 1.19 and 0.43, respectively. Anisotropy ratios for crack growth appear uncorrelated with anisotropy ratios for Charpy impact. The observed anisotropy may partially explain the difference between uniaxial and multiaxial fatigue crack growth as determined by others.